Development of a digital beamforming antenna array with single receiver - Qian, Xing (2012)
A novel type of switched smart antenna array receiver for digital beamforming is proposed. The new receiver system is advantageous in drastic reduction of hardware components to construct RF channels for the smart antenna system through the use of single pole N-throw pin diode switch (SPNT). The project is also inclusive of verification of a newly proposed time division multiplexing MIMO concept via accurately controlled experiment. This system offers an N times reduction in RF hardware for an N-element array. A two-element by ten-element prototype is built for the MIMO experiment. System principles, beamforming algorithms comparison and hardware simulation considerations are discussed. The system feasibility is verified through the mentioned MIMO test.